ANALISIS KARAKTERISTIK FILTRASI DAN EFISIENSI ADSORPSI AMONIUM PADA SISTEM FILTER BIOCHAR TERAKTIVASI Mg2+ - Dewa Agung Dibyacitta; I Gede Yudha Pratama; I Made Wahyu Wijaya (Jurnal Ecocentrism, 2026)
The increasing concentration of ammonium (NH4+) in domestic wastewater contributes to eutrophication, depletion of dissolved oxygen, and disruption of aquatic ecosystem balance. Continuous treatment systems often face operational stability challenges due to fluctuations in flow rate and pollutant loading, thereby requiring filtration technologies that are both effective and hydraulically stable. This study aimed to analyze the filtration characteristics and ammonium adsorption efficiency of an upflow Mg2+-activated biochar filter system arranged in four serial compartments. Wood-based biochar was chemically modified using a 4.2 g/L MgCl2.6H2O solution for 70 minutes. The system was operated continuously for six days at a constant flow rate of 100 mL/min using domestic wastewater with ammonium concentrations ranging from 27.74 to 42.73 mg/L. The results showed a head loss of 0.0267 m per compartment and a total of 0.1068 m, indicating stable hydraulic conditions without significant clogging. The average hydraulic retention time (HRT) was 1.79 hours per compartment (9.78 hours total), providing adequate contact time for adsorption. Ammonium adsorption efficiency reached 94.28–96.53% and increased progressively across the compartments. It can be concluded that the Mg2+-activated biochar filter system demonstrated favorable hydraulic performance and high ammonium adsorption efficiency under continuous operation.